Removal of Phosphate from Synthetic Aqueous Solution by Adsorption with Dolomite from Padalarang - Fadjari Lucia Nugroho; Lili Mulyatna; Anggi Doli Wiranata Situmeang (Journal of Engineering and Technological Sciences, 2014)
The presence of phosphate in wastewaters can cause eutrophication of surface  water bodies leading  to algal-blooming  in the aquatic environment and degradation  of  water  quality.  Phosphate  removal  from  wastewaters  by conventional biological treatment removes only 10-30% of the phosphate, whilst chemical  treatment  using  precipitants  such  as  calcium  or  iron  salts,  although effective,  is  expensive  and  produces  water-rich  sludge  which  must  be  further treated.  Hence,  phosphate  removal  by  adsorption  in  the  form  of  Ca -phosphate has been proposed as an alternative to the more traditional methods. This study investigated the feasibility of using dolomite"“a common sedimentary rock"“from Padalarang, West Java, Indonesia  as the  adsorbent  for the removal of phosphate from synthetic aqueous solution. Chemical analysis revealed that the Padalarang dolomite  contains  33.6-36.2%  CaO.  Batch  experiments  at  room  temperature indicated  that  optimum  removal  of  phosphate  was  achieved  at pH  9.  At  25°C , where  increasing  concentrations  of  phosphate  (10"“100  mg/L)  increased phosphate  adsorption  (2.15-31.3  mg/g)  by  the  dolomite.  The  adsorption  of phosphate could be described by the Langmuir isotherm model, with constants Qm= 476.19 mg/g, K L= 0,00106 L/mg and equilibrium parameter (R L): 0.904  "“ 0.989. Phosphate adsorption by dolomite not only permits its removal but also its  potential recovery for reuse.